CHEMOTHERAPY-INDUCED PERIPHERAL NEUROPATHY: A COMPREHENSIVE REVIEW OF PATHOPHYSIOLOGY, CLINICAL MANIFESTATIONS AND MANAGEMENT STRATEGIES - Aulia, Rashieka Salma; Indriawan, Ramses (Mandala Of Health, 2025)
Chemotherapy-induced peripheral neuropathy (CIPN) is a side effect of chemotherapy that damages peripheral nerves, causing sensory, motor, and autonomic abnormalities that significantly decrease the quality of life for cancer patients. Characterized by symptoms such as numbness and tingling, the incidence of CIPN can reach 68% in the first month post-therapy. The severity of this condition often forces a dose reduction or discontinuation of chemotherapy, which can compromise the effectiveness of cancer treatment. Based on this literature review of the last 10 years, CIPN is a significant clinical challenge. Therefore, comprehensive clinical guidelines for its diagnosis, symptom management, and prevention are needed to optimize cancer therapy outcomes